Characterization of nickel doped Zn7Sb2O12 spinel phase using Rietveld refinement - Gama, L.; Paiva-Santos, C. O.; Vila, C.; Lisboa Filho, Paulo Noronha [UNESP]; Longo, Elson [UNESP] (J C P D S-int Centre Diffraction Data, 2003)
Zn7Sb2O12 is known to adopt an inverse spinel crystal structure, in which Zn2+ occupies the eight tetrahedral positions and Sb5+ and Zn2+ randomly occupy the 16 octahedral positions. Samples of Zn7-xNixSb2O12 (X = 0, 1, 2, 3, and 4) were synthesized using a modified polymeric precursor method, known as the Pechini method. The crystal structure of the powders was characterized by Rietveld refinement with X-ray diffraction data. The results show that for X = 0, 1, and 2 Ni substitutes for Zn2+ in the octahedral sites, and that for X = 3 and 4 it is assumed that Ni2+ replaces Zn2+ ions in both the octahedral and tetrahedral positions. It is also observed for x = 3 and 4 the formation of two spinel phases. (C) 2003 International Centre for Diffraction Data.
Keywords: spinel structure; X-ray diffraction; Rietveld method; Pechini method